A 30‐year review of copper pitting corrosion and pinhole leaks: Achievements and research gaps. Issue 2 (31st March 2021) - Gibson, John; Karney, Bryan
Abstract: Despite decades of research, the pitting of copper pipes is poorly understood. This article summarizes the key research findings from 1990 to the present and identifies research gaps. Several lines of evidence suggest that, for soft waters, additional alkalinity or maintaining a pH <8.5 may reduce copper pitting. Phosphate corrosion inhibitors, used to prevent lead corrosion, may also moderate copper pitting in low‐alkalinity waters. However, such inhibitors could also exacerbate pitting due to insufficient coverage or could increase biological growth. Biological processes are likely involved in pitting corrosion, and practices to reduce biological growth may be beneficial. The research gaps identified include a need for better benchmarking, the effects of chemical transients (e.g., chlorine burns) and of hydraulic transients (e.g., water hammer), and changing the residual disinfectant from chlorine to chloramine. Article Impact Statement: Approximately 750, 000 pinhole leaks are estimated to occur in the United States each year, but we do not really know why.